Elementos marinos en Ramón López Velarde: un poeta que no conoció el mar - Solís Carrillo, Luis Juan (Review of International American Studies, 2015)
Maritime elements in the oeuvre of Ramon Lopez Velarde, a poet who ‘never knew the sea’ Considered by many as the ‘national poet’ of Mexico, cantor of a province traumatized by the 1910 Revolution, Ramon Lopez Velarde Jerez writes poetry abounding in maritime metaphors: boat, vessel, islands, among many other images match the voice of a poet who equated his own personality to a lamp: a sailboat-shaped vessel, which hangs in the Cathedral of San Luis Potosi. In a poetic horizon that extends between the ends of a marked dualism, Lopez Velarde aspires, as he says in one of his most celebrated poems, to ‘drop anchor in the last treasure of love’. Similarly, he speaks of a ‘curly tide’, in which ‘the sea smiles’ and ‘unstable foam is eternity’. His are wonderful, crystal-clear, images: no small thing in the case of a poet who, as they say, ‘never knew the sea’.